COGNITIVE IMPAIRMENT IN MULTIPLE SCLEROSIS: FROM PATHOPHYSIOLOGY TO TREATMENT - A LITERATURE REVIEW - Małgorzata Leśnik; Rafał Kuśmider; Hubert Kostka; Damian Dolata; Adrian Zagórski; Patrycja Wierzbowska; Jadwiga Kleinrok; Anna Bereta-Kostaś (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Cognitive impairment (CI) is a frequent and often overlooked symptom of multiple sclerosis (MS). It significantly affects patients’ quality of life, limiting daily functioning, independence, and social and professional engagement. While it can appear at any stage of the disease, it is particularly prevalent in progressive forms. The aim of this review is to present a comprehensive overview of cognitive dysfunction in MS, including its origins, clinical presentation, assessment, and management strategies. Description of the State of Knowledge: CI in MS arises from complex interactions involving immune-mediated inflammation, neurodegeneration, and structural and functional brain changes. It typically affects information processing speed, attention, memory, and executive functions. Various risk factors contribute to its severity, including disease phenotype, age, comorbidities, and lifestyle factors. Despite its high prevalence, CI is underdiagnosed due to limited routine screening. Standardized cognitive assessment tools are increasingly used in clinical practice to support timely diagnosis and monitoring of cognitive decline. Both pharmacological and non-pharmacological approaches, particularly cognitive rehabilitation, have demonstrated beneficial effects. Conclusions: Cognitive impairment should be recognized as a core symptom of MS and addressed through regular screening and individualized treatment. Early detection, interdisciplinary care, and patient education are key to reducing its impact and improving long-term outcomes.